Critical Success Factors for Online-Shops of Drugstores - Sabrina Svechla; Jessica Fischer; Hans-Michael Ferdinand (Markenbrand, 2014)
The digitalization of the every-day life also affects buying habits of customers. Changes that take place regarding these habits result in an increasing number of e-commerce retailers. Online-shops in the business-to-consumer field are especially successful with apparel and electronic products. But not every industry that goes online initially starts out as being appealing for customers. This article deals with an e-commerce field of still low frequency, online-shops of drugstores. Their success depends on two factors: the user-friendliness of the information system and the consistency of the marketing strategy. Regarding the first -user-friendliness- the focus is on the quality of the system, which includes a clear structure of and easy navigation through the online-shop. To further ensure the quality of information they need to be up to date, relevant and comprehensible. Last but not least the service quality of the information system needs to be considered by offering hotlines or FAQ-sections. Regarding the second part – consistency of the marketing strategy- it is important to initially understand consumers' behaviour throughout all buying phases and integrate these insight in a multi-channel strategy. This should combine the advantages of buying in a retail store (products can be touched) and buying online (convenience). A comparing analysis of Schlecker's and Rossmann's online-shop including the success factors above shows why drugstores are successful with e-commerce – and why not. – – Die wachsende Digitalisierung des Alltags wirkt sich auch auf die Kaufgewohnheiten der Kunden aus. Die Veränderung der Gewohnheiten spiegelt sich in der zunehmenden Anzahl an E-Commerce-Händlern wider. Online-Shops im Business-to-Consumer-Markt sind im Bereich der Bekleidungs- und Elektronikbranche sehr erfolgreich. Doch nicht jede Branche findet von Anfang an großen Anklang bei Kunden im Online-Geschäft. Der folgende Artikel befasst sich mit einem noch wenig frequentierten E-Commerce-Bereich, den Online-Shops von Drogeriemärkten. Deren Erfolg hängt von zwei Faktoren ab: der Nutzerfreundlichkeit des Informationssystems und der Durchgängigkeit der Marketingstrategie. Bei der Nutzerfreundlichkeit wird der Fokus zunächst auf die Qualität des Systems selbst gelegt, zu der etwa eine einfache Navigation und eine klare Seitenstruktur des Shops gehören. Aktualität, Relevanz und Verständlichkeit der Informationen sind wichtige Aspekte der Informationsqualität. Schließlich entscheiden Angebote wie eine Hotline oder ein FAQ-Bereich über die Servicequalität eines Informationssystems. Aus Marketingsicht sind eine gute Kenntnis des Verbraucherverhaltens über alle Kaufphasen sowie eine Multi-Channel-Strategie wichtig, die die Vorteile des Einkaufs im Ladengeschäft (Anfassbarkeit der Produkte) und des Online-Shoppings (Bequemlichkeit) miteinander verbindet. Eine vergleichende Analyse der Webshops von Schlecker und Rossmann anhand der dargestellten Erfolgsfaktoren zeigt, warum Drogeriemärkte im E-Commerce erfolgreich sind – oder nicht.
Keywords: M31; M3; L81; I12; 650; Marketing; Marketing-Kommunikation; Sales; Online-Shops; E-Commerce; Healthcare; ECommerce; Drugstores; Success Factors; B2B; Multi-Channel-Strategie; Gesundheitsversorgung; Marketing; Absatz; Vertrieb; Markenführung; Digitale Güter; Online-Handel; Drogerie; Drogeriewaren